Anti-Corruption Education in Milenial Era (Case Study in Poltekes Kemenkes Pangkalpinang) - Muhammad Seto (Faculty of Social and Political Sciences University of Bangka Belitung, 2019)
This research is conducted to describe and analyze student’s understanding of the concept of the notion of corruption, an indication of corruption, the impact and dangers of corruption against themselves, their families and the state, the risk in doing the act of corruption, the notion of anti-corruption, sense of values that indicated the behavior of Anti-corruption, and so on. The research was actualized by the implementing the Anti-corruption Culture Education, including: the implementation of Role Play on internal and external causes based on case scenarios precisely and students understand the internal and external causes. Making anti-corruption media; giving opinion on social media sites, presenting materials of anti-corruption in the Campus Dakwah Institution (LDK), posters, banners, the declaration of honest movement on examination, role plays/drama/short videos on anti-corruption in accordance with the themes were packaged in unique and interesting ways. Doing activities that demonstrated the values ​​and principles of the anti-corruption such as: honesty canteen, daily activities, conducting field surveys on public health services of the ministry of health programs, conducting field survey / visiting the Indonesian Court for Corruption Crimes, and socialization in efforts to prevent corruption. Higher Education played an active role in the anti-corruption movement by giving the anti-corruption culture that handled by educators. The role of educators were to provide the understanding and set an example in the anti-corruption movement to students by utilizing information and communication technologies which are growing increasingly sophisticated in this millennial era. College students were able to perform the anti-corruption action and got involved in supporting anti-corruption movement in the family environment, campus, local and national communities in order to create a clean, corruption-free nation.